The Analysis of Science Process Skills (SPS) of 11th Grade Science Students - Elvy Rahmi Mawarnis; Ilham Akbar; Mimi Herman (Universitas Pendidikan Mandalika, 2023)
This research is motivated by students who do not understand chemistry lessons, especially in explaining formulas and calculations. Even though the learning methods and models used by teachers are different so that students have a